Reskilling and Upskilling Strategies for Generation Z in Responding to Digital Transformation in Startup Companies - Ramadhani, Siti Nurhaliza; Fadliansyah, Ahmad (Universitas Sains dan Teknologi Komputer, 2025)
Digital transformation has led to changes primarily in the workforce's skill requirements, especially in start-up companies, where innovation plays a crucial role in driving business growth. However, it identifies Generation Z: the new upcoming dominant workforce among digital skill-gapped sections needing further work on appropriate reskills and upskills. This study analyzes the strategies, challenges, and impacts of reskilling and upskilling programs for Generation Z, addressing digital transformation in Indonesian start-ups. This research uses a qualitative, exploratory case-study design. The data were obtained from in-depth interviews, open-ended questionnaires given to 20 Generation Z respondents, and company documentation. Thematic analysis using NVivo software was used to analyze the data. Be ready? The implications suggest that upskilling is prioritized (90%) over reskilling (70%); upskilling is typically perceived as more flexible and relevant to day-to-day tasks. Major impacts include technological adjustment (85%), team collaboration (75%), and self-confidence (70%). Reskilling requirements, therefore, pose greater challenges for non-IT workers, necessitating continuous, modular program design and requiring more resources in terms of time and budget. The start-ups, therefore, focus on maximizing the use of digital platforms for training and pair it with internal mentoring to overcome this constraint. The purpose of the research is also to emphasize the appropriate nature of the training strategy, given participants' backgrounds and the distinctive context of Indonesian start-ups. Contributions to the theory include enriching the knowledge surrounding human capital and social learning. In contrast, the practical contributions intend to guide start-ups and policymakers toward framing skill-development initiatives that are increasingly inclusive, effective, and sustainable.